Primerjalna književnost danes - in jutri? - Virk, Tomo (Primerjalna književnost, 2001)
Comparative literature today - and tomorrow? The paper begins with a short description of the polemics on the role, essence and future of comparative literature as it developed around the Bernheimer Report in the mid-nineties onthe North American continent between the so-called "contextualists" and "non-contextualists". It argues for a comparative literature which follows thetradition of focusing on expressly literary issues, while complementing them with the findings of new theories. In the second part, it uses an actual example to demonstrate the fatal consequences the discipline suffers in view of the efforts by those members of the profession, who would like to take comparative literature closer to cultural studies, and points out the prospects for the development of comparative literature in the future.
Keywords: comparative literature; primerjalna književnost; literary science; literarna veda; kulturne študije; kontekstualizem; literarnost